Association Between Niacin Intake and Mortality Risks in Chronic Kidney Disease - Dr. Samuel T. Morgan; Dr. Lin Wei Zhang (International Journal of Medical Science and Public Health Research, 2025)
Background: Chronic kidney disease (CKD) is a global health issue with increasing prevalence and significant disease burden (1, 2). Patients with CKD have a substantially elevated risk of cardiovascular disease (CVD) and all-cause mortality (3, 4). Niacin, or vitamin B3, has been used to manage dyslipidemia, a common condition in CKD, but its effects on mortality in this population are unclear (5, 6, 7, 8, 9, 10, 11, 12). This study investigates the relationship between dietary niacin intake and the incidence of all-cause and cardiovascular mortality among CKD patients. Methods: We conducted a comprehensive review of existing literature, including cohort studies and post-hoc analyses of clinical trials, to evaluate the association between dietary niacin intake and mortality outcomes in CKD patients. Studies were identified through systematic searches of electronic databases. Data on niacin intake, patient characteristics, and mortality outcomes were extracted and synthesized. Results: Several studies suggest a potential link between niacin and mortality in CKD patients. While niacin has shown some benefits in managing dyslipidemia (20, 21, 22, 23, 24, 25), its impact on cardiovascular events and overall survival in CKD patients is complex. Some studies have shown that high doses of niacin did not reduce cardiovascular events and may have increased adverse effects (7, 8). A post-hoc analysis of the AIM-HIGH trial showed that extended-release niacin did not significantly affect cardiovascular events or kidney function in CKD patients (12). Other observational studies suggest a more nuanced relationship, where very low or very high intake might be detrimental (30, 31, 32, 33, 34). Conclusion: The relationship between dietary niacin intake and the risk of all-cause and cardiovascular mortality in CKD patients is not fully elucidated. While niacin plays a crucial role in various metabolic processes (28, 29), and dyslipidemia is a key risk factor in CKD (11, 13), the evidence regarding its impact on mortality in this specific population is inconclusive. Further well-designed studies are needed to determine the optimal range of niacin intake for CKD patients and to assess whether supplementation provides a net benefit in terms of reducing mortality.